Penghulu sebagai Ujung Tombak Konstruksi Pemikiran Beragama Moderat di Sintang - Nijo Nijo; Zaenuddin Hudi Prasojo (Khazanah Theologia, 2020)
The transnational religious thought of Salafi Wahabi has received a significant response from some Muslims in Sintang City. The response, among others, is marked by the establishment of a Salafi Study Center at Abu Bakr mosque that has influenced some congregations of the surrounding mosques such as al-Amin mosque, Nur Mosque, and al-Muttaqin Mosque in Kampung Ladang area. In addition, another religious thought of Jamaah Tabliqh also gets adherents from the surrounding community in Masuka. They have set up a mosque to accommodate their religious activities. The positive response to the transnational religious thought has also been found in the hinterland of Ketungau Hilir and Tempunak sub-districts in Sintang City area. This work discusses the roles of Penghulu (the official Islamic religious leaders) in Sintang District in responding to the growing of the transnational religious thought. Based on qualitative data and analysis gathered in the field, the work suggests that the marriage administers (the penghulu) have not shown their satisfying performance with well structured programs. In fact, the penghulu sets in a strategic position within the society. They have focused more on marriage counselling as their services to religious guidance to the community. Special programs for spiritual direction with a broader range of materials have not been attracting their attention due to their limited time allocated and facilities available. Therefore, this work recommends that it is urgent to initiate the construction of knowledge that is not easily to be exposed by transnational religious traditions that tend to act radically. The penghulu may better provide insight into Islamic moderation or moderate Islam to the community in the region.